Silent Crooke's cell corticotroph adenoma of the pituitary gland presenting as delayed puberty. (31st March 2017) - Giri, Dinesh; Roncaroli, Federico; Sinha, Ajay; Didi, Mohammed; Senniappan, Senthil
Summary: Corticotroph adenomas are extremely rare in children and adolescents. We present a 15-year-old boy who was investigated for delayed puberty (A1P2G1, bilateral testicular volumes of 3 mL each). There was no clinical or laboratory evidence suggestive of chronic illness, and the initial clinical impression was constitutional delay in puberty. Subsequently, MRI scan of the brain revealed the presence of a mixed cystic and solid pituitary lesion slightly displacing the optic chiasma. The lesion was removed by transphenoidal surgery and the biopsy confirmed the lesion to be pituitary adenoma. Furthermore, the adenoma cells also had Crooke's hyaline changes and were intensely positive for ACTH. However there was no clinical/biochemical evidence of ACTH excess. There was a spontaneous pubertal progression twelve months after the surgery (A2P4G4, with bilateral testicular volume of 8 mL). Crooke's cell adenoma is an extremely rare and aggressive variant of corticotroph adenoma that can uncommonly present as a silent corticotroph adenoma in adults. We report for the first time Crooke's cell adenoma in an adolescent boy presenting with delayed puberty. Learning points: Constitutional delay of growth and puberty (CDGP) is a diagnosis of exclusion; hence a systematic and careful review should be undertaken while assessing boys with delayed puberty. Crooke's cell adenomas are a group of corticotroph adenomas that can rarely present in childhood and adolescence with delayed puberty. Crooke's cell adenomas can be clinically silent but are potentially aggressive tumours that require careful monitoring.